DINAMIKA KEPERCAYAAN SEBAGAI MEDIATOR ANTARA KEPUASAN DAN LOYALITAS PASIEN DI RS GRAHA HUSADA JEPARA - Dani Hasan Saputra; Mohamad Rifqy Roosdhani (LP2M Universitas Bina Bangsa, 2024)
Healthcare providers must be adaptive in the face of healthcare industry competition by prioritizing increasing patient satisfaction as a strategy to meet increasing market demands. The goal is to increase patient trust and loyalty. This study aims to determine the effect of patient satisfaction on patient loyalty mediated by patient trust at Graha Husada Jepara Hospital. There were 127 samples in this study. The data used in this study is a type of quantitative data obtained from filling out questionnaires by selected respondents through the simple random sampling method using the slovin formula. The analysis method used in this study is the Structural Equation Model (SEM) using the SmartPLS program. The results of this study show that patient satisfaction has a positive and significant effect on patient loyalty, patient satisfaction has a positive and significant effect on patient trust, patient trust has a positive and significant effect on patient loyalty. Patient Satisfaction with Loyalty in Trust mediation also has a positive relationship